Effects of tick infestation on Boran (Bos indicus) cattle immunised against theileriosis in an endemic area of Kenya - Castro, J.J. de; Young, A.S.; Dransfield, R.D.; Cunningham, M.P.; Dolan, T.T. (1985)
Boran (Bos indicus) heifers were immunised by infection with local Theileria parva parva, T p lawrencei and T mutans stocks and treated with parvaquone and later exposed to natural tick and tick borne disease challenge in the Trans-Mara Division of Kenya. The Theileria species parasites in the challenge were maintained in African buffalo and cattle and the tick vectors were supported by several species of wild Bovidae and domestic livestock present in the area. Thirty immune cattle were observed for 30 weeks while grazing on a ranch in the Trans-Mara Division. Of these, 15 were immersed in toxaphene at weekly or twice-weekly intervals while 15 cattle remained without acaricide application. Cattle, which became pregnant, were withdrawn from the experiment. There was no evidence of any clinical tick-borne disease in either group of cattle during the experiment. Five species of ixodid ticks infested the cattle during the experiment and cattle, which were not treated with acaricide, had far more ticks. Rhipicephalus appendiculatus was the most abundant tick species, with a mean infestation of 46 adults per animal in the undipped cattle. This tick also appeared to be the cause of the observed reduction in weight gains. Major haematological parameters did not differ significantly between the groups. Behavioural studies showed that the undipped cattle spent less time grazing and ruminating. This study has shown that, at the expense of some loss in productivity, zebu cattle, immunised against ticks and theileriosis, can be kept despite tick infestation.